Pengaruh Alokasi Dana Desa Terhadap Kesejahteraan Masyarakat di Desa Pantai Mekar Kecamatan Muara Gembong Kabupaten Bekasi - Rizki, Ferdy (Cantaka: Jurnal Ilmu Ekonomi dan Manajemen, 2024)
Village Fund Allocation is one of the government's budgets intended for village communities and managed by the Village Government. The purpose of this study is to find out how the Village Fund Allocation affects the welfare of the village community in Bantargadung Village & To find out how much the Village Fund Allocation affects the welfare of the village community in Pantai Mekar Village. The method used is the Descriptive method, this method is used to take samples, The descriptive method focuses on data collection, presentation, processing and summarization. The sampling technique uses incidental sampling techniques. Data collection method with interviews and questionnaires. Data analysis uses simple linear regression analysis. The results of this study show in the T-test conducted that the allocation of village funds has a significant effect on the welfare of the village community because the Tcount > Ttable is 7.123 > 166342 and the significant result is 0.00 < 0.05. This means that the variable of village fund allocation has a significant influence on the welfare of the village community.